The Enrichment of Visual Experience through Music: Exploring Art-Music Perception - Elkoshi, Rivka (Cultural Arts Research and Development, 2025)
This study explores the interplay between visual art and classical music, focusing on the role of ekphrasis—the translation of visual art into musical form. Two types of art–music connections are investigated: ekphrastic connections, in which the music translates a single painting and retains its title, and related connections, in which the music is inspired by multiple paintings. Twenty-one adult participants without formal training in art or music engaged with three art–music pairs: two ekphrastic pairs—Kaulbach-Liszt (The Battle of the Huns) and Böcklin Rachmaninoff (The Isle of the Dead)—and one related pair: Musgrave’s Summer which draws on works by Johns, Monet, and Van Gogh. Participants were tested individually under two conditions: Unimodal (viewing the paintings alone) and Multimodal conditions (viewing paintings with accompanying music). The study examined how aesthetic impressions varied across these conditions, compared responses to ekphrastic versus related pairs, and analyzed how differences in musical duration influenced participants’ preferred listening times. A key finding revealed that Enrichment—a phenomenon in which music enhanced the perception of visual art by revealing new meanings or details—was the most common response under Multimodal conditions. This effect was consistent across both ekphrastic and related pairings. These findings highlight the potential of cross-modal artistic experiences to enrich aesthetic perception and offer insights into optimizing the presentation of art-music stimuli for lay adult audiences.